Perbaikan Mutu dan Peningkatan Produksi Ikan Mas Koki (Carrasius auratus) Melalui Rekayasa Set Kromosom - Dwi Puji Hartono; Ninik Purbosari (Politeknik Negeri Lampung., 2010)
The prominent purpose this experiment was producing superior quality of Carasius auratus, which is have to growth faster and good morphology. While particular purpose was to know temperature level effect on triploidisation on individual triploid (3n) formation of Carasius auratus and to find suitable spawning method /combination in Carasius auratus propagation but settle make high productivity. Spawning was conducted using induce breeding. Carasius auratus was spawn with support by hormone stimulation. Triploidisation was using heat shock to achieve triploid fish (3n). The same procedure was conducted to control. Heat shock temperature level was 40, 41 and 42oC. Result of this experiment showed that fish on heat shock 40oC given individual triploid presentation high more than fish on heat shock 41 and 42o C. Where as control was 100% of individual diploid. Hatching and larvae survival rate were shown value lower than control without heat shock. Keywords: Carasius auratus, quality, triploidisation